Home to health care to hospital: Evaluation of a cancer care team based in Australian Aboriginal primary care. (29th January 2019) - Ivers, Rowena; Jackson, Brad; Levett, Trish; Wallace, Kyla; Winch, Scott
Abstract: Objective: To evaluate the acceptability of a cancer care team based at an Australian Aboriginal medical service in supporting patients' cancer journeys and to assess improvements in access to cancer care. Design: The cancer care team consisted of an Australian Aboriginal health worker, counsellor and enrolled nurse employed for 2 days a week, supported by a general practitioner. The cancer care team supported patients from prediagnosis while investigations were being undertaken, at diagnosis and through treatment, such as surgery, chemotherapy and radiotherapy, and follow‐up, including to palliative care and grief support where these were required. They coordinated preventive programs, such as cervical smear and mammogram recall registers, and coordinated health promotion activities to promote prevention and early detection of other cancers, such as bowel cancer, skin cancer, liver cancer and prostate cancer. The program was evaluated qualitatively using semistructured interviews with current clients of the cancer care team and stakeholders, using grounded theory to analyse emerging themes. Setting: An Australian Aboriginal community‐controlled health service in New South Wales. Participants: The cancer care team provided care for 79 clients. Main outcome measures: Acceptability and accessibility of cancer care services. Results: The evaluation involved recruitment of eight Australian Aboriginal clients of the cancer care team and eight stakeholders. The main themes to emerge included improved accessibility of cancer care services, including availability of home visits, transport and accompaniment to tertiary settings. The service was viewed as being culturally safe. Conclusion: A primary care‐based cancer care team in an Australian Aboriginal medical service provided a culturally safe and accessible service for clients.